Enriched oxygen improves age-related cognitive impairment through enhancing autophagy - Wang, Shengyuan; Chen, Bengang; Yuan, Minghao; Liu, Shu; Fan, Haixia; Yang, Xu; Zou, Qian; Pu, Yinshuang; Cai, Zhiyou (Frontiers in Aging Neuroscience, 2024)
Age-related cognitive impairment represents a significant health concern, with the understanding of its underlying mechanisms and potential interventions being of paramount importance. This study aimed to investigate the effects of hyperbaric oxygen therapy (HBOT) on cognitive function and neuronal integrity in aged (22-month-old) C57BL/6 mice. Male mice were exposed to HBOT for 2 weeks, and spatial learning and memory abilities were assessed using the Morris water maze. We employed transcriptome sequencing and Gene Ontology (GO) term enrichment analysis to examine the effects of HBOT on gene expression profiles, with particular attention given to synapse-related genes. Our data indicated a significant upregulation of postsynapse organization, synapse organization, and axonogenesis GO terms, likely contributing to improved cognitive performance. Moreover, the hyperphosphorylation of tau, a hallmark of many neurodegenerative diseases, was significantly reduced in the HBO-treated group, both in vivo and in vitro. Transmission electron microscopy revealed significant ultrastructural alterations in the hippocampus of the HBOT group, including an increase in the number of synapses and the size of the active zone, a reduction in demyelinated lesions, and a decreased number of “PANTHOS.” Furthermore, Western blot analyses confirmed the upregulation of PSD95, BDNF, and Syn proteins, suggesting enhanced synaptic plasticity and neurotrophic support. Moreover, HBOT increased autophagy, as evidenced by the elevated levels of Beclin-1 and LC3 proteins and the reduced level of p62 protein. Finally, we demonstrated that HBOT activated the AMPK-mTOR signaling pathway, a critical regulator of autophagy. Notably, our findings provide novel insights into the mechanisms by which HBOT ameliorates age-related cognitive impairment, suggesting the potential therapeutic value of this approach.